2015
DOI: 10.1016/j.circir.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma maligno primario del sistema nervioso central: un reto diagnóstico

Abstract: The primary malignant melanoma of the central nervous system is extremely rare. There are features in magnetic resonance imaging that increase the diagnostic suspicion; nevertheless there are other tumors with more prevalence that share some of these features through image. Since there is not an established therapeutic standard its prognosis is discouraging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Nevertheless, the prognosis of primary CNS melanoma appear to be better than metastatic brain examples, particularly if localized and if complete resection is possible. In these cases, the median survival is 20.7 months [12]. In our case, despite we did not know the nature of the lesion before surgery, we made a complete resection of the lesion as it is shown in control image test (Fig.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, the prognosis of primary CNS melanoma appear to be better than metastatic brain examples, particularly if localized and if complete resection is possible. In these cases, the median survival is 20.7 months [12]. In our case, despite we did not know the nature of the lesion before surgery, we made a complete resection of the lesion as it is shown in control image test (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…The main location of melanocytes is in the piamatter around inferior surface of the cerebellum, spinal medulla, and high cervical medulla. According to Quillo-Olvera et al, the most common locations of primary brain melanoma are the lobe (53.1 %), posterior fossa (17.3 %), and pineal region (13.6 %) [12]. Vijayalaxmi et al did a search between 1989 and 2014, and they found 19 cases of primary CNS melanoma, none of them at the insular region [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2345] It is often described in association with cutaneous melanosis. [16] In the central nervous system (CNS), melanoma is often described in relation to leptomeninges termed as leptomeningeal melanosis. [7] The imaging or histopathological features with recent advances in the immunohistochemical markers do not contribute to distinguish primary from metastatic melanomas that made these patients to undergo thorough investigation.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The imaging or histopathological features with recent advances in the immunohistochemical markers do not contribute to distinguish primary from metastatic melanomas that made these patients to undergo thorough investigation. [26] The lack of guidelines regarding adjuvant treatment in dealing with these tumors results in poor outcome with inevitable recurrences despite complete surgical excision. [3]…”
Section: Introductionmentioning
confidence: 99%